A comprehensive examination of the optical morphologies of 719 isolated galaxies in the AMIGA sample. Issue 2 (28th June 2019) - Buta, Ronald J; Verdes-Montenegro, Lourdes; Damas-Segovia, Ancor; Jones, Michael; Blasco, Javier; Fernández-Lorenzo, Mirian; Sanchez, Susana; Garrido, Julian; Ramirez-Moreta, Pablo; Sulentic, Jack W
Abstract: Using images from Sloan Digital Sky Survey Data Release 8, we have re-examined the morphology of 719 galaxies from the Analysis of the interstellar Medium in Isolated GAlaxies (AMIGA) project, a sample consisting of the most isolated galaxies that have yet been identified. The goal is to further improve the classifications of these galaxies by examining them in the context of the Comprehensive de Vaucouleurs revised Hubble-Sandage (CVRHS) system, which includes recognition of features that go beyond the original de Vaucouleurs point of view. Our results confirm previous findings that isolated galaxies are found across the complete revised Hubble sequence, with intermediate- to late-type (Sb-Sc) spirals being relatively more common. Elmegreen Arm Classifications are also presented, and show that more than 50 per cent of the 514 spirals in the sample for which an arm class (AC) could be judged are grand design (AC 8, 9, 12). The visual bar fraction for the sample is ≈50 per cent, but only 16 per cent are classified as strongly barred (SB). The dominant family classification is SA (non-barred), the dominant inner variety classification is (s) (pure spiral), and the dominant outer variety classification is no outer ring, pseudo-ring, or lens. The Kolmogorov–Smirnov test is used to check for potential biases in the morphological interpretations, and for any possible relation between rings, bars, and ACs with local environment and far-infrared excess. The connection between morphology and stellar mass is also examined for a subset of the sample.